THE EFFECT OF SUPPORT FROM ORGANIZATIONS AND TRANSFORMATIONAL LEADERSHIP ON AFFECTIVE COMMITMENT OF EMPLOYEES OF INDUSTRIAL ENTERPRISES OF VIETNAM - V. N. Knyazev; Le Thi Minh Loan; Pham Minh Son (Вестник университета)
He result of a survey of 547 workers at Vietnamese industrial enterprises shows that the organizational support and the transformation leadership have a positive and statistically significant correlation with emotional commitment. The results of the regression analysis confirm that the organizational support has more influence than the transformational leadership on emotional commitment. In addition, the social package and charisma have the strongest effect on emotional commitment. This study also showed that transformational leadership has a moderating effect on the interaction between organizationalal support and emotional commitment. The study suggests some recommendations to improve the workers’s emotional commitment to the organization.